1982
DOI: 10.1099/00221287-128-11-2715
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Adenosine of Aggregation Centre Initiation and Cyclic AMP Binding in Dictyostelium

Abstract: The inhibitory action of adenosine on the initiation of aggregation centre formation in starving Dictyostelium discoidem was examined and used to test assumptions of theoretical models of cyclic AMP signalling. Adenosine at 5 mM strongly inhibited aggregation centre initiation without preventing signal relay. Inosine or AMP at 10 mM had no effect and did not prevent the effect of adenosine. Adenosine had no effect on cellular phosphodiesterase activity, contact site A formation, or chemotaxis to small drops of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…IPA belongs to the group of adenosine derivatives that have been shown to affect binding of cAMP to the cAMP-specific surface receptors [18]. However, we have found that the course of aggregation in the presence of IPA differs considerably from that observed in the presence of adenosine [19]. Although the cells on IPA agar relay the cAMP signal, and optical density waves can be observed in dark-field as in the case of adenosine [19], the cells never form any characteristic streaming patterns due to a concerted cell movement.…”
Section: Introductionmentioning
confidence: 46%
See 2 more Smart Citations
“…IPA belongs to the group of adenosine derivatives that have been shown to affect binding of cAMP to the cAMP-specific surface receptors [18]. However, we have found that the course of aggregation in the presence of IPA differs considerably from that observed in the presence of adenosine [19]. Although the cells on IPA agar relay the cAMP signal, and optical density waves can be observed in dark-field as in the case of adenosine [19], the cells never form any characteristic streaming patterns due to a concerted cell movement.…”
Section: Introductionmentioning
confidence: 46%
“…However, we have found that the course of aggregation in the presence of IPA differs considerably from that observed in the presence of adenosine [19]. Although the cells on IPA agar relay the cAMP signal, and optical density waves can be observed in dark-field as in the case of adenosine [19], the cells never form any characteristic streaming patterns due to a concerted cell movement. Instead, the waves vanish after a certain time leaving the cell layer in a homogeneous state.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In wild-type cells, cAMP induction of prespore gene expression is inhibited by millimolar concentrations of adenosine and by micromolar concentrations of the adenosine analogs NECA and IPA, which cannot be phosphorylated by an extracellular adenosine kinase (37,42,43). Adenosine also inhibits cAMP binding (24,41), and recent studies showed that only binding of cAMP to cAR1, but not to cAR2 or cAR3, is inhibited by adenosine (17a). To identify the cAR that mediates prespore gene induction and to verify that the inhibitory effects of adenosine are due to inhibition of cAMP binding FIG.…”
Section: Resultsmentioning
confidence: 99%
“…In Dictyostelium, cyclic AMP acts as a chemoattractant, a morphogen, and a mediator of gene regulation (Bonner, 1970;Konijn et al, 1968;Lodish et al, 1982). It has been suggested that the product of 5NT activity, adenosine, is involved in the regulation of development (Newell and Ross, 1982;Schaap and Wang, 1986;Spek et al, 1988;Theibert and Devreotes, 1984;. It is particularly interesting that a phosphatase activity becomes localized to a narrow region of cells at the interface of the prestalk-prespore boundary during development (Aramaki et al, 1980;Armant and Rutherford, 1979;Krivanek, 1956).…”
mentioning
confidence: 98%